The complete catalogue of the National Museum of Art, Osaka 1977-2003. (Osaka : National Museum of Art Osaka, 2004)
Abe, Hiraomi ; Abe, Nobuya ; Agano, Machiko ; Aigasa, Masayoshi ; Akana, Hiroshi ; Akasegawa Genpei ; Akioka, Miho ; Akiyama, Yoh ; Akiyama, Yutokutaishi ; Amano, Kunihiro ; Anderson, Laurie ; Ando, Nana ; Ando, Tsuguo ; Antes, Horst ; Anzai, Shigeo ; Aohara, Toshiko ; Aoki, Noe ; Aoyama, Ryusui ; Appel, Karel ; Arai, Tomoo ; Arakawa, Shusaku ; Araki, Takako ; Araki, Tetsuo ; Arcangero, Ianelli ; Arman ; Armitage, Kenneth ; Arp, Hans (Jean) ; Artaud, Antonin ; Asada, Hiroshi ; Asano, Moufu ; Asaoka, Kay-ko ; Assetto, Franco ; Aviado, Virgilio ; Awazu, Kiyoshi ; AY-O ; Azumo, Kengiro ; Baba, Akira ; Baba, Kashio ; Bacadale, Mario ; Balka, Miroslaw ; Balkenhol, Stephan ; Bando, Soichi ; Baselitz, Georg ; Basquiat, Jean-Michel ; Becher, Bernd & Hilla ; Bellini, Mario ; Belloli, Carlo ; Bense, Max ; Bernik, Janez ; Beuys, Joseph ; Bito, Yutaka ; Blake, Peter ; Boeri, Cini ; Bohnen, Blythe ; Bonetto, Rodolfo ; Bontecou, Lee ; Borofsky, Jonathan ; Breer, Robert ; Bremer, Claus ; Brown, James ; Buren, Daniel ; Burkhardt, Klaus ; Bustamante, Jean-Marc ; Byars, James Lee ; Cage, John ; Calder, Alexander ; Calle, Sophie ; Campigli, Massimo ; de Campos, Augusto ; Cane, Louis ; Caro, Anthony ; Castellani, Enrico ; Ceroli, Mario ; César ; Cézanne, Paul ; Cha, Kea-Nam ; Chamberlain, John ; Chiba, Sho ; Childs, Bernard ; Chiyokura, Osyu ; Christo ; Chuma, Yasufumi ; Clave, Antoni ; Cobbing, Bob ; Copley, William ; Coral, Flaviano ; Cornell, Joseph ; Crippa, Roberto ; Cucchi, Enzo ; Decursu, Giorgio ; Demachy, Robert ; Demand, Thomas ; Dine, Jim ; Dixon, James ; Döhl, Reinhard ; Domoto Yuumi ; Domoto, Hisao ; Downing, Joe ; Dubuffet, Jean ; Duchamp, Marcel ; Dumitrescu, Sorin ; Duvillier, René ; Echizenya, Yoshitaka ; Edison, Laurie Toby ; El Q ; Emi, Kinuko ; etc.
Engels
Japans
boek
Keywords: Japan